Synthesis, Characterization and Biological Activities of Some Organotin(IV) Complexes - Rehman, Wajid; Muhammad, Bakhtiar; Hassan, Zonera; Khan, Jamil; Bashir, Nadia; Khan, Abdullah; Hammed, Gulzar (Asian Journal of Chemistry, 2010)
Organotin(IV) complexes with the general formulae R3SnL (R: alkyl and L: Schiff base) have been prepared and the bonding in these complexes were studied through various spectral techniques like IR, 1H and 13C NMR. The alkyl and phenyl groups attached to the tin(IV) atom have been assigned by the comparison of experimental chemical shifts with those calculated data. The novel complexes and the ligand, soluble in dimethyl sulphoxide have been screened against various types of bacteria for their antibacterial activity.